2021
DOI: 10.1108/ijefm-03-2020-0015
|View full text |Cite
|
Sign up to set email alerts
|

Antecedents and consequences of satisfaction among participants in health-affiliated charity sport events

Abstract: PurposeUnderstanding factors that enhance participants' satisfaction has become critical to developing effective donor retention strategies for charity sport events (CSEs). However, there is a lack of empirical research on participants' satisfaction with CSEs. The purpose of this study is to examine the antecedents and consequences of satisfaction among CSE participants and to empirically test the relationships between the proposed constructs.Design/methodology/approachData were collected from 238 participants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 50 publications
(130 reference statements)
1
6
0
3
Order By: Relevance
“…Achieving hedonic satisfaction, that is, a sufficient emotional connection known as a warm glow, leads to repeat participation, which reflects participants' loyalty to an event (Tsai, 2020). This is consistent with the findings of Park et al (2021), who found that participants' perceptions of the prosocial impact, sense of belonging and trust in charity sports events all had a strong positive impact on how satisfied they felt about the activities, which in turn led to loyalty. Helping others can further promote consumers' awareness of the social value, creating a warm glow and enhancing the consumer experience, leading to the return of consumers in the future (Hartmann et al , 2017).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Achieving hedonic satisfaction, that is, a sufficient emotional connection known as a warm glow, leads to repeat participation, which reflects participants' loyalty to an event (Tsai, 2020). This is consistent with the findings of Park et al (2021), who found that participants' perceptions of the prosocial impact, sense of belonging and trust in charity sports events all had a strong positive impact on how satisfied they felt about the activities, which in turn led to loyalty. Helping others can further promote consumers' awareness of the social value, creating a warm glow and enhancing the consumer experience, leading to the return of consumers in the future (Hartmann et al , 2017).…”
Section: Discussionsupporting
confidence: 91%
“…A charity sports event is a specially organized charity that connects sports and causes. Activities at these events primarily include endurance sports such as cycling, running, or swimming, which are organized to raise money through registration fees to help with causes such as education, health and the environment (Palmer and Dwyer, 2020; Park et al , 2021). The most popular charity-affiliated sports event has been the charity run (Zouni et al , 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…It is suggested that if a person has set goals to help with social issues and they know that the donations from an event have been used to support the issues, they will feel more satisfied because it confirms that the good deed has been successfully undertaken [14,51]. It also results in participants experiencing increased warm glow [52].…”
Section: Discussionmentioning
confidence: 99%
“…Several instruments are used to try to explain it by considering different dimensions: SERVQUAL [ 34 ], a model by Rust and Oliver [ 35 ], and sub-dimensions [ 36 , 37 , 38 , 39 ]. Specific models are used in the field of sports management: SPORTSERV [ 40 ], EVENQUAL) [ 41 ], SEQSS [ 38 ], EPOD, and EPOD2 [ 42 , 43 ], which also introduce dimensions specific to each sporting event or service [ 25 , 27 , 44 , 45 , 46 , 47 ]. Furthermore, taking into account that perception may vary from spectators to participants [ 31 ], some analyses focus on spectators [ 14 , 44 , 48 , 49 , 50 ], and others on participants [ 13 , 17 , 30 , 51 , 52 , 53 ].…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…This represents the main reason why the analysis of the quality of sporting events is increasingly considered in related scientific studies. Research on the connection between perceived quality (PQ) and perceived value (PV), general satisfaction (GS), and loyalty has almost always been addressed from the point of view of the sports viewer [ 12 , 13 , 14 , 15 , 16 ], but fewer studies address it from the perspective of the athlete [ 13 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ], who is also a co-creator of value and quality of the event with their participation [ 28 , 29 ]. These studies analyze quality in a static way without considering that the perception of the athlete may vary with experience and over time.…”
Section: Introductionmentioning
confidence: 99%